Unpublished Omen Reports Texts From the Old Babylonian Period - صبي احمد ناجي; نايف سمراء حميد (مجلة دراسات في التاريخ والآثار, 2022)
Publication and edition of two tablets from the library in the Ebabbar Temple of Sippar, a manuscripts represent a Babylonian extispicy reports for the god marduk. The texts of this article belong to the texts discovered during the eighth excavation campaign of Baghdad University at Sippar in the twenty-fourth excavation season . As it was among the texts discovered in Room No. 1 and it belongs to the Old Babylonian Period, especially from the time of the King Ammi Saduqa (reigned 1646-1626 BC ) .dated to the years .[i] [i] - For a detailed account of this excavation see: • Fadhil and Z. R. Al-Samarraee., «Excavation in Sippar (Tell Abu Habbah) - preliminary report on the excavation results of the 24th campaign 2002», BaM 36 (2005), pp. 157-224. See also • Fadhil and Z. R. Al-Samarraee., «The results of the 24th Excavation campaign in the city of Sippar », Sumer 52 (2002/03), pp. 294-357, (in Arabic).